Analysis of the Role of Sustainability Accounting on the Financial Performance of Port Services Companies - Shobiq Zainudin; Driana Leniwati; Nazaruddin Malik (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the role of sustainability accounting on the financial performance of a port services company through the implementation of Environmental, Social, and Governance (ESG). The study used a qualitative method with an explanatory case study approach at a port services company in the Tanjung Perak area, Surabaya. Data were obtained through in-depth interviews, observations, and analysis of company documents related to sustainability practices and financial performance during the 2021–2025 period. The results show that the company has implemented sustainability accounting comprehensively with an ESG score of 95.7%. From an environmental perspective, the port facility electrification program has successfully increased fuel efficiency and reduced carbon emissions. From a social perspective, human resource development and corporate social responsibility programs have contributed to increased stakeholder trust. Meanwhile, from a governance perspective, the application of good corporate governance principles, supported by ISO 37001 and ISO 22301 certifications, has strengthened the company's credibility. ESG implementation has been shown to drive operational efficiency, increase port service volume, and strengthen the company's reputation, which has an impact on improving financial performance. These findings indicate that sustainability accounting not only functions as a reporting instrument, but also as a business strategy that is able to create sustainable economic, social, and environmental value and support the company's long-term competitiveness.